Metabolic Enzymes Moonlighting in the Nucleus: Metabolic Regulation of Gene Transcription. Issue 8 (August 2016) - Boukouris, Aristeidis E.; Zervopoulos, Sotirios D.; Michelakis, Evangelos D.
Abstract : During evolution, cells acquired the ability to sense and adapt to varying environmental conditions, particularly in terms of fuel supply. Adaptation to fuel availability is crucial for major cell decisions and requires metabolic alterations and differential gene expression that are often epigenetically driven. A new mechanistic link between metabolic flux and regulation of gene expression is through moonlighting of metabolic enzymes in the nucleus. This facilitates delivery of membrane-impermeable or unstable metabolites to the nucleus, including key substrates for epigenetic mechanisms such as acetyl-CoA which is used in histone acetylation. This metabolism–epigenetics axis facilitates adaptation to a changing environment in normal (e.g., development, stem cell differentiation) and disease states (e.g., cancer), providing a potential novel therapeutic target. Trends: Many cytoplasmic metabolic enzymes (including all essential glycolytic enzymes) and mitochondrial enzymes moonlight in the nucleus. Their nuclear function includes canonical (production of the metabolite they normally produce) and non-canonical functions, independent of catalytic activity, such as kinase activity or DNA binding to regulate gene transcription and DNA repair. The nuclear production of metabolites is important. For example, acetyl-CoA is produced in mitochondria and is crucially needed for histone acetylation in the nucleus, but is not permeable through mitochondrial membranes and, owing to its high-energy status and instability, needs to be produced close to where it is needed. These nuclear metabolic enzymes provide the basis of an emerging metabolism–gene transcription axis, which includes epigenetic regulation (histone acetylation, histone and DNA methylation). Growing evidence suggests that this axis optimizes adaptive responses linking metabolic stress to cellular functions such as proliferation or differentiation.